Regional significance of the Debrecen International Airport - Váczi, Péter (Acta Agraria Debreceniensis, 2013)
In the following essay I would like to examine the Debrecen International Airport’s reginonal status, significance and development opportunities. Furthermore, I would like compare the passenger traffic of Debrecen’s airport with other regional airports in Middle-East Europe during the 2005–2012 period. In the second part of my essay, I would like to share the experience of my questionnaire survey and a possible future perspective for the Debrecen International Airport.